2007
DOI: 10.1103/physrevlett.99.166402
|View full text |Cite
|
Sign up to set email alerts
|

Spin Gap and Luttinger Liquid Description of the NMR Relaxation in Carbon Nanotubes

Abstract: Recent NMR experiments by Singer et al. [Singer et al. Phys. Rev. Lett. 95, 236403 (2005).] showed a deviation from Fermi-liquid behavior in carbon nanotubes with an energy gap evident at low temperatures. Here, a comprehensive theory for the magnetic field and temperature dependent NMR 13 C spin-lattice relaxation is given in the framework of the Tomonaga-Luttinger liquid. The low temperature properties are governed by a gapped relaxation due to a spin gap (∼ 30 K), which crosses over smoothly to the Luttinge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 27 publications
4
38
0
Order By: Relevance
“…9 The TLL and its characteristic power-law scaling have been confirmed by transport studies, 10 VB PES, 8 and nuclear magnetic resonance ͑NMR͒. 11 Alkali-metal intercalation has been demonstrated to shift the Fermi level into the conduction band ͑CB͒ of graphite. 12 In this way the CB becomes accessible to VB methods such as angle-resolved PES.…”
Section: Introductionmentioning
confidence: 86%
“…9 The TLL and its characteristic power-law scaling have been confirmed by transport studies, 10 VB PES, 8 and nuclear magnetic resonance ͑NMR͒. 11 Alkali-metal intercalation has been demonstrated to shift the Fermi level into the conduction band ͑CB͒ of graphite. 12 In this way the CB becomes accessible to VB methods such as angle-resolved PES.…”
Section: Introductionmentioning
confidence: 86%
“…(9) and (10)] the time integral of the real part of these correlations from t = 0 to t = +t 0 is required. Numerical results are taken at discrete times which are multiples of the time step δt chosen for the real-time evolution within tMPS.…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…[24][25][26][27] For the case of ultrathin diameter 4-Angstrom metallic SWCNTs, experimental observation of the Meissner effect in 2001 1 has prompted some theoretical works exploring the possibility of superconductivity being the ground state of the system. While some authors predicted Peierls ground state, [28][29][30][31][32] others predicted superconductivity. [33][34][35][36][37][38][39][40] More recently, the observation of the superconducting electrical transition for arrays of aligned 4-Angstrom nanotubes (embedded in AFI zeolite crystals) has shown that the resistance drop is precipitated by a BerezinskiiKosterlitz-Thouless (BKT)-like transition [41][42][43] in the plane perpendicular to the c-axis of the nanotubes, thereby facilitating a 1D to 3D crossover that leads to bulk superconductivity [2][3][4] at low temperatures.…”
Section: Introductionmentioning
confidence: 99%